Józef Lobodowski: un poeta polaco exiliado en España - Bak, Grzegorz (Revista de Filología Románica, 2002)
The short biography of Józef L_ odowski. L_ obodowski in Spain: his life and works. Spanish themes in his poetry. L_ obodowski poetry as a «bridge» between Caucasus and Iberian Peninsula. The importance of the exiled writer for Slavonic Philology in Spain and Hispanic Philology in Poland.